Aetiology of Headache: A Prospective Observational Study from Southern India - B Naveen Kumar; J Dianitta Devapriya Veronica (Journal of Clinical and Diagnostic Research)
Introduction: Headache is a widely prevalent symptom that greatly affects the quality of life. Yet, the disability caused by headache disorders does not receive the attention it deserves. Identifying the exact aetiology and classifying headaches helps focus on appropriate treatments that can reduce their burden on individuals and society. Aim: To examine the common aetiologies of headaches and estimate the prevalence of rhinologic and non rhinologic headaches. Materials and Methods: The present prospective observational study was carried out in the Otorhinolaryngology Outpatient Department (OPD), Yashoda Hospital, Hyderabad, Telangana, India, between December 2016 and December 2018. The study included 140 patients aged 16-55 years who presented with complaints of headache. These patients underwent a complete general and clinical examination and were subsequently investigated to classify the cause of their headaches as either rhinologic or non rhinologic, as well as, acute or chronic. Those classified under rhinologic headaches who required surgery were subjected to surgical intervention. The other causes of headache were treated accordingly. The treatment response of chronic headache cases was followed-up for a period of six months to observe for complete remission of symptoms. Statistical analysis was performed using International Business Machines (IBM) Statistical Package for the Social Sciences (SPSS) software version 27.0, statistics for Windows, (IBM Corporation, New York, United States, 2021). Results: Out of total 140 participants included in the study, 80 (57.14%) were males and 60 (42.85%) were females. The overall mean±Standard Deviation (SD) age of the study population was 34±9.66 years. Of the 140 patients included in the study, 44 (31.42%) had acute headaches and 96 (68.57%) had chronic headaches. Among the acute cases, 22 (50%) were due to acute sinusitis. Among the chronic headaches, 33 (34.37%) were cases of chronic migraine. Conclusion: Headache is a common clinical symptom with different aetiopathogeneses, mandating proper evaluation, which helps in the precise diagnosis of the disease and appropriate management. The study results showed acute sinusitis as the most common cause of acute headache and chronic migraine as the most common cause of chronic headache.